Principles and Contents Of Developing Patriotic Dignity In Students - Yusupovich, Mirzakarimov Xudaberdi (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
This article expresses the principles of education and training in development, the patriotic dignity of students and its importance in the process of education.